1993
DOI: 10.1002/jcb.240510207
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of DNA replication in isolated nuclei initiated by an aprotinin‐binding protein

Abstract: Isolated cell nuclei were used as the source of template DNA to investigate the role of a cytosolic aprotinin-binding protein (ADR) in the initiation of eukaryotic DNA replication. Computerized image cytometry demonstrated that the DNA content of individual nuclei increased significantly following incubation with ADR-containing preparations, and the extent of DNA synthesis is consistent with that allowed by the limiting concentration of dTTP. Thus, dTTP incorporation into isolated nuclei represents DNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…A remarkable conclusion of this study is that a narrow zone of active replication initiation, referred to as oriGNAI3, has been identified both by a 2D gel electrophoresis and a competitive PCR technique. This differs from the data obtained for the Chinese hamster DHFR and human rDNA loci, in which broad zones of initiation, at least 30 kb in length, were disclosed by 2D gels (13,14), whereas narrow regions were observed with other replicon mapping techniques (5,6,8,(16)(17)(18)(19).…”
Section: Comparison With Other Mammalian Initiation Zones Analyzed By...contrasting
confidence: 99%
See 2 more Smart Citations
“…A remarkable conclusion of this study is that a narrow zone of active replication initiation, referred to as oriGNAI3, has been identified both by a 2D gel electrophoresis and a competitive PCR technique. This differs from the data obtained for the Chinese hamster DHFR and human rDNA loci, in which broad zones of initiation, at least 30 kb in length, were disclosed by 2D gels (13,14), whereas narrow regions were observed with other replicon mapping techniques (5,6,8,(16)(17)(18)(19).…”
Section: Comparison With Other Mammalian Initiation Zones Analyzed By...contrasting
confidence: 99%
“…While precise mapping of this preferential region was not attempted, Little et al observed that the strongest bubble arc signals were located in an ∼8 kb long region of the broad initiation zone (14). Interestingly, alternative techniques later mapped a 1.5 kb long (17) or a 4 kb long (18) initiation region within the preferential region identified by 2D gels (14). Thus oriGNAI3 and the origin at the rDNA locus appear to share similar properties, if one considers either that infrequent initiation events were below the threshold of detection in our 2D NA study or that the degree of preferential initiation is higher at the initation region described here.…”
Section: Comparison With Other Mammalian Initiation Zones Analyzed By...mentioning
confidence: 99%
See 1 more Smart Citation
“…sequences encoding a 13-kb primary transcript and a 30 kb segment referred to as the non-transcribed spacer (NTS). Replication analyses suggest that replication initiation occurs in the NTS, preferentially in a 5 kb-long region upstream, and a 2 kb-long region downstream of the rRNA genes (51)(52)(53)(54)(55). Flexibility analysis shows that all peaks map exclusively within the NTS, with two and three peaks respectively located within the initiation region downstream or upstream the genes (Fig.…”
Section: Peaks Of Enhanced Flexibility At Mammalian Dna Replication Omentioning
confidence: 95%